Implementation of Risk-Based Business Licensing in Improving Legal Compliance of Business Actors in Sibolga City - Abdillah Afandi Paranginangin; Lilawaty Ginting (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the implementation of Risk-Based Business Licensing through the Online Single Submission Risk-Based Approach (OSS-RBA) system in Sibolga City from the perspective of the government and business actors, and identify obstacles that influence the increasing legal presence of business actors. The study uses an empirical legal method with a descriptive-analytical juridical-sociological approach. Data were obtained through interviews, observations, and literature studies, then analyzed qualitatively using an interactive analysis model. The results show that the implementation of OSS-RBA has driven the transformation of licensing services towards a faster, more transparent, and integrated risk-based digital system. From the government's perspective, OSS-RBA provides benefits in the form of administrative efficiency, business data integration, and permit issuance. Meanwhile, business actors gain ease of business legalization through the publication of a Business Identification Number (NIB). However, the implementation of OSS-RBA still faces various legal and non-legal obstacles, such as regulatory requirements, weak supervision, low digital literacy, limited technological infrastructure, and a low legal culture in the business community. Therefore, the success of OSS-RBA is not only measured by the number of permits issued, but also by its ability to build legal awareness and a culture of legal business in society.